Influence of Classroom Acoustics on Noise Disturbance and Well-Being for First Graders - Astolfi, Arianna; Puglisi, Giuseppina Emma; Murgia, Silvia; Minelli, Greta; Pellerey, Franco; Prato, Andrea; Sacco, Tiziana (Frontiers in Psychology, 2019)
Several studies have shown so far that poor acoustics inside classrooms negatively affects the teaching and learning processes, especially at the lowest grades of education. However, the extent to which noise exposure or excessive reverberation affect well-being of children at school in their early childhood is still unanswered, as well as their awareness of noise disturbance. This work is a pilot study to investigate to which extent classroom acoustics affects the perceived well-being and noise disturbance in first-graders. About 330 pupils aged from 6 to 7 years participated in the study. They belonged to 20 classes of 10 primary schools located in Torino (Italy), where room acoustic measurements were performed and where noise level was monitored during classes. The school buildings and the classrooms were balanced between socio-economic status and acoustic conditions. Trained experimenters administered questionnaires in each class, where pupils answered all together during the last month of the school year (May). Questions included the happiness scale, subscales assessing self-esteem, emotional health, relationship at home and with friends, enjoyment of school, intensity and noise disturbance due to different sound sources, quality of voice. The findings of the study suggest that long reverberation times, which are associated to poor classroom acoustics as they generate higher noise levels and degraded speech intelligibility, bring pupils to a reduced perception of having fun and being happy with themselves. Furthermore, bad classroom acoustics is also related to an increased perception of noise intensity and disturbance, particularly in the case of traffic noise and noise from adjacent school environments. Finally, happy pupils reported a higher perception of noise disturbance under bad classroom acoustic conditions, whereas unhappy pupils only reported complaints in bad classroom acoustics with respect to the perception of pleasances with himself or herself and of fitting in at school. Being mother tongue is a children characteristic that brings to having more chance of attending classes in good acoustics, of being less disturbed and having more well-being, and richer districts presented better acoustic conditions, resulting in turn that richer districts also revealed a greater perception of well-being.